Komparasi Fatwa Wahbah Zuhaili dan Muhammad Zuhaili tentang Perkawinan Misyār - Abdulhakim, Luqman; Yusran Sibawaih; Rahmat Hidayat; Muh Rajib (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article aims to discuss the comparison of fatwas between Wahbah Zuhaili and Muhammad Zuhaili on misyār marriage. There are differences in fatwas between Wahbah Zuhaili and his brother Muhammad Zuhaili on misyār marriage. This research is a type of library research, descriptive-comparative in nature with a comparative approach. The data collection method of this research uses documentation and data analysis techniques using comparative analysis. The results of the study state that there is a dispute between the fatwas of Wahbah Zuhaili and Muhammad Zuhaili regarding misyār marriage. Wahbah Zuhaili argues that misyār marriage is permissible as long as it is registered in court. Wahbah Zuhaili allows this marriage with the argument that the contract of this marriage is in accordance with Sharia. In contrast, Muhammad Zuhaili prohibits misyār marriage. Muhammad Zuhaili argues that this marriage is not in accordance with the purpose of marriage according to Islamic law and there are indications of exploiting women. The difference that occurs is only due to differences in views regarding the validity of marriage. Wahbah Zuhaili considers a valid marriage to be one whose contract is in accordance with sharia. Muhammad Zuhaili emphasizes more on the purpose of marriage in seeing the validity of a marriage. In Islamic law, this marriage is basically valid because it does not violate sharia as long as the purpose does not deviate.